2020
DOI: 10.1002/hep.31057
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Prediagnostic Concentrations of Circulating Sex Steroid Hormones and Liver Cancer Among Postmenopausal Women

Abstract: Background and Aims In almost all countries, incidence rates of liver cancer (LC) are 100%‐200% higher in males than in females. However, this difference is predominantly driven by hepatocellular carcinoma (HCC), which accounts for 75% of LC cases. Intrahepatic cholangiocarcinoma (ICC) accounts for 12% of cases and has rates only 30% higher in males. Hormones are hypothesized to underlie observed sex differences. We investigated whether prediagnostic circulating hormone and sex hormone binding globulin (SHBG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…11 Another recent study from the Liver Cancer Pooling Project (LCPP) reported that higher levels of circulating oestradiol in women were associated with an increased ICC risk. 12 Taken together, these results suggest that factors that affect oestrogenic regulation may play a role in the aetiology of ICC.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…11 Another recent study from the Liver Cancer Pooling Project (LCPP) reported that higher levels of circulating oestradiol in women were associated with an increased ICC risk. 12 Taken together, these results suggest that factors that affect oestrogenic regulation may play a role in the aetiology of ICC.…”
mentioning
confidence: 79%
“…In epidemiologic investigations of circulating sex steroid hormones and ICC risk, two studies have reported higher levels of circulating oestradiol in both men and women cholangiocarcinoma cases compared to controls. 11,12 One of these studies was based in the LCPP and reported that a doubling of circulating oestrogen levels in women was associated with a 40% increased ICC risk. 12 Neither study reported associations with circulating androgen levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that about 42,810 individuals will be diagnosed with liver cancer in the United States in 2020, of whom 30,160 will die [ 2 ]. In virtually all countries, males exhibit incidence and mortality rates 2 to 3 times higher than women [ 1 , 3 ]. As such, addressing the high mortality and poor prognosis associated with liver cancer remains an urgent priority.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, some other studies have reported no significant prognostic differences between males and females [ 8 ]. Some recent studies have reported that estrogen may play a role in the prognosis of patients with liver cancer [ 10 12 ], while others have reported no such effect [ 3 ]. Unfortunately, most—if not all—of these studies were performed using a pool of patients in surgical and non-operative states, even though surgery is a vital factor influencing patient prognosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%